KETAHANAN KELUARGA MASYARAKAT NAGARI LAGAN KECIL MUDIK KECAMATAN LINGGO SARI BAGANTI PESISIR SELATAN - Vinta Arvilia; Afnibar Afnibar; Prima Kurniati Hamzah (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
This research aims to describe the family resilience of the Nagari Lagan Kecil Mudik Community, Linggo Sari Baganti pesisir selatan. The research method used in this research is a qualitative research method. The type of qualitative research used in this research is descriptive qualitative. The research subjects in this study were housewives. Research subjects were determined using purposive sampling technique. Data collection techniques through observation and interviews. Research findings show that; Family resilience is seen from three aspects, namely a) the aspect of physical resilience, where in this aspect the eight informants' needs for food and clothing are met by the way they work, in that there is a wife who supports her husband's work. However, there is one informant who does not have a house, because they still live with their parents. b) the aspect of social resilience which can be seen from the way they gradually instill religious values in the family, namely by praying, fasting and treating other people well, c) the aspect of psychological resilience can be seen from the way they deal with problems in the family by calm yourself down first, then solve it as quickly as possible and find a solution together so that there are no misunderstandings. Always control your emotions positively by looking for something busy and not listening to bad words from other people.